'Ser teudo de responder' or 'ter de responder': on the emergence of deontic uses of 'ter de (que)' + INF in Portuguese - Brocardo, Maria Teresa (2020)
This proposal is part of an ongoing diachronic research on ter and haver (‘have’) in Portuguese, focusing in particular on the emergence of deontic constructions with ter. In this article I analyze data retrieved from a diachronic corpus and discuss the chronology and conditioning factors of the changes involved in both the disuse of ser teudo de [have-passive Prep] INF, a construction largely attested in Portuguese past stages, and the innovation ter de [have Prep] INF. Both constructions appear to have similar deontic readings, yet the datasuggest that they are not diachronically linked, the latter appearing only in a much later period. Following the presentation of theoretical and methodological issues, the retrieved data are described and discussed, the main conclusions being that: the obsolescence of ser teudo appears to be related to morphophonological factors (probably among others); the modal construction ter de INF emerged late in Portuguese and is probably a variant of ter que INF; ter que INF, the original deontic construction, emerged by reanalysis of structures where que was originally a relative pronoun (referring the object of ter), in ambiguous contexts which favored the new interpretation of the structure as a modal construction.